Pour une étude interdisciplinaire et sémio-linguistique de la viralité dans les médias - Alain Rabatel (MediAzioni)
The article aims at problematizing the notion of virality by, firstly, promoting an interdisciplinary approach to viral phenomena in order to circumscribe the influence of digital technologies, digital uses and the contemporary societal evolutions on the creation and circulation of messages. Secondly, it identifies a set of semio-linguistic characteristics likely to favour the virality of memes, and especially a weakening of the relationship to truth, the role of the hypernarrativity of messages, the ability to divert or creatively turn around somebody else’s speech, in a condensed format with shocking images, phrases that hold attention and attract the eye. These features, oriented on the referencing of the object, lead to a relative enunciative effacement and discrete enunciative postures. They favour sharing, provoke the over-significance and emotional saturation of viral messages, in connection with ideological and ethical, aesthetic and playful over-investments. When they emerge on a shared common background, all these parameters prove to be good predictors of viral dynamics on socio-numerical networks.